Nisin E Is a Novel Nisin Variant Produced by Multiple Streptococcus equinus Strains - Ivan Sugrue; Daragh Hill; Paula M. O’Connor; Li Day; Catherine Stanton; Colin Hill; R. Paul Ross (Microorganisms, 2023)
Nisin A, the prototypical lantibiotic, is an antimicrobial peptide currently utilised as a food preservative, with potential for therapeutic applications. Here, we describe nisin E, a novel nisin variant produced by two Streptococcus equinus strains, APC4007 and APC4008, isolated from sheep milk. Shotgun whole genome sequencing and analysis revealed biosynthetic gene clusters similar to nisin U, with a unique rearrangement of the core peptide encoding gene within the cluster. The 3100.8 Da peptide by MALDI-TOF mass spectrometry, is 75% identical to nisin A, with 10 differences, including 2 deletions: Ser29 and Ile30, and 8 substitutions: Ile4Lys, Gly18Thr, Asn20Pro, Met21Ile, His27Gly, Val32Phe, Ser33Gly, and Lys34Asn. Nisin E producing strains inhibited species of Lactobacillus, Bacillus, and Clostridiodes and were immune to nisin U. Sequence alignment identified putative promoter sequences across the nisin producer genera, allowing for the prediction of genes in Streptococcus to be potentially regulated by nisin. S. equinus pangenome BLAST analyses detected 6 nisin E operons across 44 publicly available genomes. An additional 20 genomes contained a subset of nisin E transport/immunity and regulatory genes (nseFEGRK), without adjacent peptide production genes. These genes suggest that nisin E response mechanisms, distinct from the canonical nisin immunity and resistance operons, are widespread across the S. equinus species. The discovery of this new nisin variant and its immunity determinants in S. equinus suggests a central role for nisin in the competitive nature of the species.